Heart rate and lactate response of junior handball players (Under 18) during competitive match play - Gupta, S.; Goswami, A. (International Journal of Applied Exercise Physiology, 2017)
Background: This study highlights the heart rate (HR) and blood lactate (La) response of junior handball players of two positions - wings and backs, during competitive matches. Methods: Heart rate and blood lactate of twelve handball players - 6 Backs (B) and 6 Wingers (W)] - were recorded in quarter- and semifinal matches of the tournament. HR was recorded continuously by heart rate telemeter whereas La was measured at rest, after warm up and immediately after the end of first- and second halves of the matches. Results: Average HR and Maximum Heart Rate Reserve (MHRR) of the players were similar in each half of play. No significant difference (p<0.05) in average HR and MHRR were observed between B (169±17.5 beats/min and 74.3±9.4%) and W (169.5±16.3 beats/min and 74.1±8.5%). W and B played about 1/5th of their playing time above the Anerobic Threshold level. Average HR of the players in each 5 min of play could vary significantly but no such difference per 15 min of play was found. Lactate of W and B after the first half of play were 7.4±1.6 and 7.2±1.5 mM and after the end of the matches were 7.9±0.4 and 7.6±1.4 mM respectively. No significant difference in La was found between W and B. Conclusion: (a) Handball play is a high intensity game, (b) the workload does not vary between W and B, (c) the intensity of play could vary in every 5 min of play but there is no difference in average intensity for each 15 min, and (d) handball is played aerobically for majority of the time.